MOLECULAR PHYLOGENETIC ANALYSIS OF THE RANUNCULACEAE FAMILY PLANTS BASED ON DNA BARCODING IN THE KARAGANDA REGION FLORA - Zhumabay, N.B.; Sutula, M.Y.; Ishmuratova, M. Y.; Bekkuzhina, S.S.; Manabayeva, S.A. (Eurasian Journal of Applied Biotechnology, 2025)
The Ranunculaceae family is one of the most diverse groups of angiosperms, including species of high ecological and pharmacological significance. In this work, a molecular phylogenetic analysis of 19 Ranunculaceae species from the flora of the Karaganda region, including the rare and protected species Anemone patens, Adonis volgensis and Adonis vernalis, was carried out. The rbcL, matK, trnH-psbA, and ITS markers were used for the study, and phylogenetic trees were constructed using the maximum likelihood (ML) method with bootstrap support. The results showed that the ITS marker had the highest discriminatory ability at the species level (17.64%), while rbcL, matK, and trnH-psbA provided reliable classification at the tribe and genus level. Phylogenetic analysis confirmed a clear separation of the subfamilies Thalictroideae and Ranunculoideae with high bootstrap support (0.87 and 0.90, respectively). Within the Ranunculoideae, the tribes Ranunculeae, Anemoneae, Delphinieae, and Adonideae formed stable clades (>0.84). Anemone patens was clearly distinguished at the species level (0.97). The data obtained clarify the taxonomic relationships of Ranunculaceae in the region and emphasize the need for the combined use of multiple DNA markers. For the first time, this study provides molecular data on rare species of Ranunculaceae in Kazakhstan, which is important for their monitoring and conservation.